2019
DOI: 10.1017/s0068245419000121
|View full text |Cite
|
Sign up to set email alerts
|

Arachne's Web: Women, Weaving and Networks of Knowledge in the Bronze Age Southern Aegean

Abstract: The appearance of loom weights at a number of southern Aegean sites in the Middle and early Late Bronze Age is indicative of the adoption of a new weaving technology: the use of the warp-weighted loom. The specific type of loom weight (discoid) recovered is a Cretan form, and this evidence of Cretan influence is also seen in a wider range of material culture features at these settlements during this period. Weaving is a complex skill and learning requires contact between novice and expert practitioner over an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Recent ethnoarchaeological studies showed how repetitive actions stemming from the manufacture of earthen building materials result in a multi-sensory experience that conditions the mind and help to develop kinaesthetic motor skills and tactile sensibility (Jerome et al 1999;Marchand 2011). Similar studies on ceramic production have emphasized the importance of nondeclarative knowledge often expressed through motor skills and implicit learning (Abell 2020;Cutler 2019;Gosselain et al 2009;Squire 2004;Warnier 2007).…”
Section: Earthen Chaîne Opératoire In the Eastern Mediterraneanmentioning
confidence: 86%
See 1 more Smart Citation
“…Recent ethnoarchaeological studies showed how repetitive actions stemming from the manufacture of earthen building materials result in a multi-sensory experience that conditions the mind and help to develop kinaesthetic motor skills and tactile sensibility (Jerome et al 1999;Marchand 2011). Similar studies on ceramic production have emphasized the importance of nondeclarative knowledge often expressed through motor skills and implicit learning (Abell 2020;Cutler 2019;Gosselain et al 2009;Squire 2004;Warnier 2007).…”
Section: Earthen Chaîne Opératoire In the Eastern Mediterraneanmentioning
confidence: 86%
“…Thus, a 'communities of practice' approach allows us to investigate skill transfer at the synchronic and diachronic level within the same community and between multiple sites (Abell 2020;Knappett & van der Leeuw 2014, 82). By sharing their knowledge, members of a community can increase the general social-based knowledge and develop motor skills essential for craft specialization (Cutler 2019;Lave & Packer 2011;Lave & Wenger 1991). In their assertion that 'a community of practice is a set of relations among persons, activity and world over time and in relation to other tangential and overlapping communities of practice', Lave and Wenger (1991, 115) propounded how the learning process is not just a top-down approach but often also works horizontally within communities.…”
Section: Introductionmentioning
confidence: 99%
“…Men were definitely more likely to leave their households for several months than women. In general, the mobility of women is determined by very different factors (see Cutler 2019, 86–8; Murray, Chorghay and MacPherson 2020, 230–1).…”
Section: Potters’ Mobility – Motivations Scales and Destinationsmentioning
confidence: 99%
“… 50 It is interesting to think about difficulties connected to the ‘unlearning’ of previously acquired techniques, pointed out by Cutler (2019) in her discussion of the transmission of technology related to textile production.…”
mentioning
confidence: 99%
“…skals et al 2015), multidyscyplinarne analizy szeregu źródeł pośrednich pozwoliły na odtworzenie kluczowej roli produkcji włókienniczej w gospodarkach kultur egejskich (np. Barber 1991;tzachili 1997;Burke 2010;Nosch, laffineur 2012;Harlow et al 2014;shaw, chapin 2016;†cutler 2021). liczne pozostałości narzędzi włókienniczych umożliwiają szacunkowe określenie parametrów przędzionych nitek, a następnie tkanin (andersson strand, Nosch 2015), rozmieszczenie narzędzi wskazywać może na skalę i organizację produkcji (Ulanowska, siennicka 2018), a także na procesy społeczne towarzyszące przekazywaniu umiejętności wytwórczych ( †cutler 2019).…”
unclassified